Single Port Gynecologic Laparoscopic and Robotic-Assisted Surgery - Marchand, Greg (IntechOpen, 2021)
This is the first ever textbook completely devoted to single-incision minimally invasive gynecologic surgery. Expert gynecologic surgeons have collaborated to produce well-referenced and thought-provoking chapters on all common single-incision techniques in use today, including laparoscopic, robotic, and vaginal, with special sections devoted to hysterectomy and gynecologic oncology procedures. Chapter topics range from the history and fundamentals of procedures to a full technical instruction manual for step-by-step execution of common procedures. This text is designed for advanced gynecologic surgeons as well as fellows in minimally invasive gynecologic surgery fellowship programs.